Platelet Functional Testing Via High‐Throughput Microtiter Plate‐Based Assays. Issue 2 (14th February 2023) - Tamang, Hem Kumar; Stringham, Emily N.; Tourdot, Benjamin E.
Abstract: Platelets play a critical role in hemostasis and thrombosis; therefore, in vitro assays that measure platelet reactivity are fundamental tools to gain insight into these physiologic processes, to diagnose platelet disorders, and to develop antithrombotic therapies. However, conventional platelet assays such as aggregometry, the clinical gold standard for assessing platelet function, are low throughput and require specialized equipment. Since platelets have a finite life span ex vivo, processes to miniaturize and multiplex assays allow a much broader overview of platelet function in significantly less time than conventional assays. Several groups have developed simplified, high‐throughput approaches to quantify platelet activation with standard laboratory equipment to lower the barrier of entry to study platelet biology. This article describes a panel of optimized and validated high‐throughput microplate assays to comprehensively assess platelet functionality, independently or in combination, to increase throughput and reduce costs. Specifically, following stimulation of platelets, a plate reader can be used to measure light transmission aggregation via absorbance; dense‐granule secretion based on ATP‐dependent luminescence generation; and cytosolic calcium levels with a cell‐permeant, fluorescent Ca 2+ ‐sensitive dye. Additionally, platelets are an easily accessible component of the blood that share signaling pathways with other cells, making them ideal for high‐throughput drug screens. The highly adaptable and complementary assays presented in this article can be used to decipher the molecular mechanism underlying platelet activation or to identify novel inhibitors. © 2023 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Microtiter plate–based light transmission aggregometry Basic Protocol 2 : Measuring dense‐granule secretion in high‐throughput microplate assays Basic Protocol 3 : Microtiter plate–based calcium mobilization Support Protocol : Platelet isolation and enumeration